MAHRAM DAN KAWIN SESUKU DALAM KONTEKS HUKUM ISLAM (KAJIAN TEMATIK AYAT-AYAT HUKUM KELUARGA) - Arisman Arisman (JURIS (Jurnal Ilmiah Syariah), 2018)
Mahram is an important problem in Islam because it can influence the behavior, halal and haram. In addition, mahram is a wise decision from Allah the almighty and it is also a perfection of this religion which manages all aspects of life. As a result, it is a must for us to know whom belongs to mahram and his right. Futhermore, mahram also reached the problem of in-tribe married. The problem is whether it is considered as an opposit opinion toward the existence of mahram or not. This problem is always debated by many religion experts and it has emerged many different groups of schools and also one punished another who prohibited in-tribe married case. As a conclusion the writer declared that this problem is not part of daruriyyat, but it is just a hajiyyat category. In another word we can say that in-tribe married is allowed in Islam.